Aswamedha: A Legitimation of Leadership Based on The Kitab of Aswamedha Parwa | Aswamedha: Sebuah Legitimasi Kepemimpinan Berbasis Kitab Aswamedha Parwa - Bagas Sukma Priyambodo; I Ketut Ardana; Sutrisni - (GHURNITA: Jurnal Seni Karawitan, 2022)
The legitimacy model with ceremonial means is rarely done nowadays, therefore it is necessary to re-narrate the legitimacy model with ceremonial means. The purpose of this creation research is to reveal the content and interpret the leadership legitimacy model in the Aswamedha Parwa book through musical compositions. This creation research uses Art Transformation Theory, which is to transform original works (literature) into new works (karawitan composition). The research method used is Practice as Research through Performance. This practice is analogous to a representation of the musical context, namely the analogy of leadership using the pathetan form, the analogy of sadness using the sendhon, the analogy of legitimate leadership using the ada-ada form. The stages that must be passed are, Pre-Working, Working on, Post-Working. The results of the analysis related to the content of the composition are the values that a leader must have so that his leadership becomes legitimate. These values have implications for an interpretation of a compositional model that prioritizes beauty as a means of representation of the musical context.